Metal casting computer-aided design and analysis - Ravi, B (PHI Learning Private Limited, 2010)
This book presents a scientific approach to metal casting design and analysis supported by software tools. Unlike other books in metal casting focused only on the process know-how, this book uncovers the know-why as well. Besides serving the needs of students of mechanical, production and metallurgical engineering, this book is equally meant to benefit practicing engineers involved or interested in casting development, including product designers, toolmakers, foundry engineers, supply chain managers, engineering consultants, researchers, and software developers. The theory discussed in the book is applicable to all types of castings: ferrous and non-ferrous, produced in sand and metal moulds. By gaining a better understanding of the theory and logic involved through creating, analysing and optimizing virtual castings, the readers will learn how to: - Design process-friendly cast products, leading to shorter development time - Manufacture assured quality castings, leading to fewer rejections and 'surprises' - Manage material and energy utilization, leading to higher yield and lower costs.